Differentiation of induced pluripotent stem cell–derived neutrophil granulocytes from common marmoset monkey (Callithrix jacchus). Issue 1 (25th November 2016) - Schrimpf, Christopher; Wrede, Christoph; Glage, Silke; Hegermann, Jan; Backhaus, Samantha; Blasczyk, Rainer; Heuft, Hans‐Gert; Müller, Thomas
Abstract : BACKGROUND: Inherited and acquired marrow failure syndromes most commonly lead to defect in myeloid and/or neutrophil differentiation and/or function. Besides this, neutropenia induced by cancer‐adjusted chemotherapy is a frequent clinical problem. In both cases, cell replacement therapy is a well‐established, but due to necessity of donors limited and perilous procedure. Therefore, autologous cell replacement from patients' own marrow‐derived cells lowers risk and bares new possibilities for therapy. Since the immune system of the marmoset monkey is known to show high similarity to humans, preclinical studies with these animals bare high hopes for immunologic research and cell replacement therapy. STUDY DESIGN AND METHODS: Marmoset‐induced pluripotent stem (iPS) cells (cj‐iPSC) were first cultivated on mouse embryonic feeder cells in medium containing recombinant human vascular endothelial growth factor. After 13 days, CD34+/vascular endothelial growth factor receptor‐2 (VEGFR2)– cells were sorted, treated with interleukin (IL‐3), thrombopoietin, and stem cell factor for 20 days and further cultivated with granulocyte–colony‐stimulating factor (G‐CSF) and IL‐3 for 10 days. RESULTS: CD34+/VEGFR2– cells could be generated in high amounts (39.65 ± 6.01%; 2.31 × 10 5 cells). Afterward, these hematopoietic progenitors could be successfully differentiated into mature cj‐iPSC–derived neutrophils showing similar morphology, specific surface antigens, and neutrophil‐specific gene products and in vitro phagocytic activity. CONCLUSION: cj‐iPSC–derived neutrophils bare high hopes in hematologic cell replacement therapy. They exhibit high morphologic similarity to native neutrophils and present neutrophil‐specific surface antigens, antimicrobial proteins, and gene products yielding an auspicious approach for continuative experiments including tests in living animals.